Five year screening on occurrence of vaccine-preventable diseases in rural Anantapur - D, Giri; Zachariah, Seeba; Thomas, Dixon (Indian Journal of Pharmacy Practice)
Objective: The main objective of the study was to screen the occurrence of Vaccine- preventable disease (VPD) in the rural Anantapur area in South India by reviewing the diseases treated in the most popular referral hospital in the area. Methods: Results & Discussion: Conclusion: Screening of patients' records of five year period (2006-2010) was done to find the occurrence of VPDs. Significance of gender variation on occurrence of measles was assessed by paired t-test. Microsoft Excel was used for tabulation and graphs. All the children born in the hospital had 100% adherence to first schedule of the vaccination. The complete schedule for the vaccination of children up to 5 years is given free of cost, but still there were no full adherence to vaccination because of reasons such as unawareness, relocating from the mother's house to father's house after delivery and following the vaccination in other health care facilities etc. There was no gender discrimination in the access to vaccines. Eighty two cases of VPD were reported in the hospital from 2006-2010. On an average 16 VPD were observed per year. Among them most commonly observed diseases, measles accounts for 56 cases in five years. Adherence to vaccination was high for the first schedule. Measles was the most common VPD observed in rural Anantapur region. There were no cases of polio, diphtheria and tetanus reported in the period of 2006-2010. The limitations of the study include not identifying the occurrence of hepatitis B infection due to lack of information about type of hepatitis. It was also not sure that the patients with VPDs were properly vaccinated or not due to unavailability of their vaccination cards.
Keywords: Immunization; DPT; OPV; BCG; hepatitis B; occurrence